Pengaruh Gaji, Tunjangan dan Fasilitas Kerja Terhadap Kinerja Karyawan Perkebunan Sawit - Alvita, Alysia; Paul Karolus Pasaribu, Johni; Nanda Utami, Febby (Journal of Trends Economics and Accounting Research, 2024)
Employees become an important asset for every company. Similarly, Asian Agri considers employees important considering the large number of employees it has. The company's success is supported by good employee performance. Many ways can be done to improve employee performance, such as increasing salaries, providing benefits, and also supporting work facilities. This study aims to determine the effect of salary, benefits, and work facilities on the performance of Jambi Asian Agri Regional employees. The research method used was quantitative and all employees were made into a population of 57 people with a sample of 50 respondents. Data collection using questionnaires and data analysis methods using classical assumption tests, multiple linear regression analysis, and determination coefficient testing. The conclusion of the results of this study is that salary negatively affects employee performance, while benefits and work facilities have a positive effect on employee performance. All results of the description of employee performance variable (Y) statement items are in the high category, which means that the average respondent's answer to the statement item is on a scale of 3.41 – 4.20. This shows that the statement items of this research can help assess employee performance.